Schwannoma Misdiagnosed as Adrenal Adenoma: A Case Report and Review of the Literature - Mussa H. AlMalki; Metib Alotaibi; Mohammad Maswood Ahmad; Muhammad Amin ur Rahman; Turki Alharthi (Case Reports in Endocrinology)
Schwannoma is a benign neurogenic tumor originating from the neural sheath of Schwann cells. It is an extremely rare cause of adrenal adenoma which is very difficult to diagnose preoperatively. We report the case of a right adrenal schwannoma discovered incidentally in a 62-year-old woman during evaluation of right flank pain. The biochemical and hormonal evaluations were unremarkable. Radiological examination revealed a 4.8 cm lesion keeping with right adrenal adenoma. Surgical intervention was done due to the large size of the tumor, and laparoscopic right adrenalectomy was performed. The postoperative course was uneventful. Histological examination established the diagnosis of schwannoma, which was further confirmed by immunohistochemical staining. In conclusion, adrenal schwannoma is extremely rare and can be misdiagnosed as nonsecreting adrenal adenoma. Complete surgical excision is the treatment of choice which is associated with favorable outcome and also helps in clarifying its histopathological nature.